Creating English Letter and Announcement Applications as Learning Tools for High School Students - Hidayat, Rohmat; Ma'arif, Iin Baroroh; Thohari, Mohammad Rahman Bagus; Fatmawati, Aida (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2024)
ABSTRACT The purpose of this research was to develop ELENA, an Android learning application to promote independent learning and advance student writing abilities specifically regarding letters and announcements. The researcher utilized the Research and Development methodology to build the application, following Maribe Branch’s ADDIE model of analysis, design, development, implementation, and evaluation during the creation process. The intended users were 11th grade students at SMK Ar-Rahman Peterongan Jombang. Data collection involved interviews and questionnaires. Expert media evaluation indicated a 97.91% suitability score, meaning the application provided an interesting and interactive platform to learn English. The material expert’s 87.5% score confirmed appropriate educational content for the learning objectives. The 87.7% implementation score showed increased student engagement and activity applying letter and announcement writing skills. Students were more motivated to write in English on those topics while using the technology. Final assessment demonstrated the application’s success at elevating writing proficiency in the target formats of letters and announcements for the participant group based on the metrics utilized in the study. In summary, this customized mobile learning solution enabled independent study and led to measurable writing gains related to the specified skills of letters and announcements for the sample 11th grade vocational high school students. KEYWORDS: Learning Media; ELENA; Writing; Letters and Announcements; Senior High School.   ABSTRAK Penelitian ini bertujuan untuk mengembangkan ELENA, sebuah aplikasi pembelajaran berbasis ICT yang dirancang untuk mempromosikan pembelajaran mandiri dan meningkatkan kemampuan menulis siswa, khususnya dalam menulis surat dan pengumuman. Penelitian ini menggunakan metodologi Penelitian dan Pengembangan, mengikuti model ADDIE dari Maribe Branch yang mencakup analisis, desain, pengembangan, implementasi, dan evaluasi dalam proses pembuatannya. Aplikasi ini ditujukan untuk siswa kelas XI di SMK Ar-Rahman Peterongan Jombang. Data dikumpulkan melalui wawancara dan kuesioner. Evaluasi oleh ahli media menunjukkan skor kesesuaian sebesar 97,91%, yang mengindikasikan bahwa aplikasi ini menawarkan platform yang menarik dan interaktif untuk belajar bahasa Inggris. Skor 87,5% dari ahli materi menunjukkan bahwa konten edukasi yang disediakan sesuai dengan tujuan pembelajaran. Skor implementasi sebesar 87,7% menunjukkan peningkatan keterlibatan dan aktivitas siswa dalam menerapkan keterampilan menulis surat dan pengumuman. Siswa lebih termotivasi untuk menulis dalam bahasa Inggris mengenai topik-topik tersebut saat menggunakan aplikasi ini. Penilaian akhir menunjukkan bahwa aplikasi ini berhasil meningkatkan kemahiran menulis siswa dalam format surat dan pengumuman sesuai dengan metrik yang digunakan dalam penelitian. Secara keseluruhan, solusi pembelajaran mobile yang disesuaikan ini memungkinkan pembelajaran mandiri dan memberikan peningkatan kemampuan menulis yang terukur dalam keterampilan surat dan pengumuman bagi siswa kelas XI di sekolah menengah kejuruan. KATA KUNCI: Media Pembelajaran, ELENA, Writing, Surat dan Pengumuman, SMA.